A drastic shift in the energetic landscape of toothed whale sperm cells - Alves, LQ; Ruivo, R; Valente, R; Sánchez Calabuig, María Jesús; Gutiérrez-Adan, Alfonso; Castro, L Filipe C; Fonseca, Miguel M; Machado, André M; Plön, Stephanie; Monteiro, Nuno; García-Parraga, David; Ruiz-Díaz, Sara (Current Biology, 2021)
Mammalian spermatozoa are a notable example of metabolic compartmentalization.1 Energy in the form of ATP production, vital for motility, capacitation, and fertilization, is subcellularly separated in sperm cells. While glycolysis provides a local, rapid, and low-yielding input of ATP along the flagellum fibrous sheath, oxidative phosphorylation (OXPHOS), far more efficient over a longer time frame, is concentrated in the midpiece mitochondria.2 The relative weight of glycolysis and OXPHOS pathways in sperm function is variable among species and sensitive to oxygen and substrate availability.3, 4, 5 Besides partitioning energy production, sperm cell energetics display an additional singularity: the occurrence of sperm-specific gene duplicates and alternative spliced variants, with conserved function but structurally bound to the flagellar fibrous sheath.6,7 The wider selective forces driving the compartmentalization and adaptability of this energy system in mammalian species remain largely unknown, much like the impact of ecosystem resource availability (e.g., carbohydrates, fatty acids, and proteins) and dietary adaptations in reproductive physiology traits.8 Here, we investigated the Cetacea, an iconic group of fully aquatic and carnivorous marine mammals, evolutionarily related to extant terrestrial herbivores.9 In this lineage, episodes of profound trait remodeling have been accompanied by clear genomic signatures.10, 11, 12, 13, 14 We show that toothed whales exhibit impaired sperm glycolysis, due to gene and exon erosion, and demonstrate that dolphin spermatozoa motility depends on endogenous fatty acid β-oxidation, but not carbohydrates. Such unique energetic rewiring substantiates the observation of large mitochondria in toothed whale spermatozoa and emphasizes the radical physiological reorganization imposed by the transition to a carbohydrate-depleted marine environment. Depto. de Medicina y Cirugía Animal Fac. de Veterinaria TRUE pub